P-T path development derived from shearband boudin microstructure - Rodrigues, B. C. (2016)
This work focuses on the development of a regional P-T-path from the Malpica-Lamego Ductile Shear Zone, NW Portugal, based on the microstructures of shearband boudins evolved during progressive simple shear. The combination of microstructural analysis, fluid inclusion studies, crystallographic pre- ffered orientation and fractal geometry analyses, allows to link several stages in the internal evolution of the boudin to regional P-T conditions. The boudinage process is initiated under differential stress after the original layer achieved sufficient viscosity contrast relative to the surrounding matrix. Two main transformations occur simultaneously: i) change in the external shape with continuous evolution from tabular rigid body to sigmoidal asymmetric morphology (shearband boudin) and ii) localized dynamic recrystallization in the sharp-tips of the structure (acute edge of shearband boudin), and along the boudin's margin and grain boundaries. Smaller recrystallized grains, particularly in the sharp-tip do- mains, accommodate most of the external strain, and larger relict grains are preserved in the centre. Dynamic recrystallization under constant strain rates and strain partitioning inside the boudins is indicated by fractal geometry based on grain boundary and grain area analysis. Progressive deformation leads to the generation of structural and textural heterogeneous domains inside the boudins, and is recorded by quartz c-axis orientation analysis and fluid inclusion studies. The last deformation episode shows the final formation of the blunt-tip domain and internal secondary shear planes. The regional P-T path begins with the crystallization of andalusite after an internal shearband boudin dilation event and ends with quartz dynamic recrystallization on boudin tips. The main deformation stage (310/315 Ma) led to reactivation of internal secondary shear zones with sillimanite crystallization.